2014 Jefferson Lecture IN THE Humanities Walter Isaacson. - M. H. (Humanities)
The article discusses the lecture "The Intersection of the Humanities and the Sciences" delivered by Walter Isaacson, president and chief executive officer (CEO) of nonprofit organization the Aspen Institute, at the John F. Kennedy Center for the Performing Arts in Washington, D.C. on May 12, 2014. Topics discussed include Ada Lovelace, the first computer programmer, the ways science informed statesman Benjamin Franklin's ideas about government, and the imagination of scientist Albert Einstein.